The Types of Argument Structure Used by Hillary Clinton in the CNN Democratic Presidential Debate - Anggie Angeline; Nani Indrajani T. (K@ta: A Biannual Publication on the Study of Language and Literature, 2009)
This qualitative research was conducted to examine the types of argument structure by Hillary Clinton in part one of the CNN Democratic Presidential Debate since Hillary, who had a great deal of experiences in political parties, was supposed to be able to construct convincing arguments that had good argument structures. The theories used to analyze were Bierman and Assali’s (1996), King’s (n.d.) and Stanlick’s (2003). The findings showed that there were five types of argument structure used: serial, linked, convergent, divergent, and hybrid argument structures. The linked argument structure was the argument structure used the most frequently in Hillary’s utterances in the debate, while the divergent was the least one. Thus, it could be concluded that Hillary’s speech in the Presidential Debate was quite interesting since she could combine all the five types of argument structure, though the frequency of using them was not the same and it seems that linked argument structure was the most effective strategy for her in arguing about the politic, economy, and social issues.